A mechanism concept and design of reconfigurable robot for rescue operation - Uddin, Md. Nasir; Rahman, Md Ahbubur; Rashid, Muhammad Mahbubur; Nithe, N. A.; Rony, J. I. (Global Journals Inc. (USA), 2016)
There seem to be a lot of robots that have been built up until today. Basically, the creation of robot is supposed to be a helper for a human. Robot will replace human whenever the task is really difficult or dangerous to be done by human. Recently, the robots that have been created were made reconfigurable. The purpose is to make the robot to function in more type of surroundings rather than only one surrounding. With this ability, the robot can be more useful to human, and less number of robot is required to complete a certain task. This report emphasizes on the reconfigurable robot project, where in this report, the robot that has been created is using the walking motion. It presents a description with pictures and construction drawings of a fourleg reconfigurable robot.